Corticotropin-Releasing Hormone (CRH) Gene Family Duplications in Lampreys Correlate With Two Early Vertebrate Genome Doublings - Cardoso, João C. R.; Bergqvist, Christina A.; Larhammar, Dan (Frontiers in Neuroscience, 2020)
The ancestor of gnathostomes (jawed vertebrates) is generally considered to have undergone two rounds of whole genome duplication (WGD). The timing of these WGD events relative to the divergence of the closest relatives of the gnathostomes, i.e., the cyclostomes, has remained contentious. Lampreys and hagfishes are extant cyclostomes whose gene families can shed light on the relationship between the WGDs and the cyclostome-gnathostome divergence. Previously, we have characterized in detail the evolution of the gnathostome corticotropin-releasing hormone (CRH) family and found that its five members arose from two ancestral genes that existed before the WGDs. The two WGDs resulted, after secondary losses, in one triplet consisting of CRH1, CRH2 and UCN1, and one pair comprised by UCN2 and UCN3. All five genes exist in representatives for cartilaginous fishes, ray-finned fishes, and lobe-finned fishes. Differential losses have occurred in some lineages. We present here analyses of CRH-family members in lamprey and hagfish by comparing sequences and gene synteny with gnathostomes. We found five CRH-family genes in each of two lamprey species (Petromyzon marinus and Lethenteron camtschaticum) and two genes in a hagfish (Eptatretus burgeri). Synteny analyses show that all five lamprey CRH-family genes have similar chromosomal neighbors as the gnathostome genes. The most parsimonious explanation is that the lamprey CRH-family genes are orthologs of the five gnathostome genes and thus arose in the same chromosome duplications. This suggests that lampreys and gnathostomes share the same two WGD events and that these took place before the lamprey-gnathostome divergence.